Factors affecting health seeking behaviour in hypertensive patients of Imenti North sub county, Kenya - Mwenda, Annarita Kajuju; Kirigia, Consolata; Kamweru, Paul Kuria; Gitonga, Lucy Kawira (International Journal Of Community Medicine And Public Health, 2020)
Background: Prevalence of non-communicable diseases like hypertension is raising hence a burden to low resource countries like Kenya. Purpose of the study was to determine factors affecting health seeking behaviour in hypertensive patients in Imenti North sub county, Kenya. Methods: A cross-sectional study design and cluster random sampling method was used to select five health facilities for study. Purposive sampling was used to select total of 212 patients from selected health facility proportionally. Spearman’s Rho correlation and bivariate logistic regression was used to check for strength of associations. Results: Patients interviewed had an average of 51 years and higher proportions were above 40 years of age. Married and female patients were (66.5%), and 60% respectively. An average of (42%) had a secondary level of education. Knowledge on lifestyle modification strategies was above average (68%). Conclusions: Health education given during hypertensive clinics had positive influence. Slow service delivery, long queues and the long waiting times for laboratory investigation results influenced patients’ health seeking behavior negatively. The study recommends the government of Kenya to develop policies on implementation of support groups among hypertensive patients in all hospitals and intensify campaigns on importance of seeking medical attention early. This will empower the patients on knowledge of hypertension management. The study also recommends health care providers to ensure reduced waiting time for the patients.